2002
DOI: 10.1038/sj.ejcn.1601357
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing energy intake and body weight loss after gastric bypass

Abstract: Objective: The gastric bypass-induced quantitative and qualitative modifications of energy intake (En In, kcal=day) and their impact on body weight (bw) loss were evaluated. The factors influencing energy intake and body weight loss were also investigated. Design: Longitudinal study. Setting: University Hospital of Geneva. Subjects: Fifty obese women undergoing a Roux-en-Y gastric bypass. Results: The reduction of EnIn was significantly related to bw loss expressed either in kg or as percentage correction of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 26 publications
6
58
0
4
Order By: Relevance
“…As already shown, 10,25,26 baseline BMI is independently negatively associated with EWL. But to date, all authors have failed to identify baseline metabolic factors associated with the success of bariatric surgery.…”
Section: 23supporting
confidence: 51%
“…As already shown, 10,25,26 baseline BMI is independently negatively associated with EWL. But to date, all authors have failed to identify baseline metabolic factors associated with the success of bariatric surgery.…”
Section: 23supporting
confidence: 51%
“…In addition, it is clear that the final body weight and/or a possible weight relapse are greatly influenced by the energy intake at the stabilization period. The reduction of energy intake is the main effect of this surgical intervention: 30 in a previous study, 31 we demonstrated that postoperative food intake shows a great individual variability and is influenced by age; in the present study, we suggest that sympathetic excitability could also play a role in the control of energy intake during the stabilization period.…”
Section: Discussionmentioning
confidence: 68%
“…Together with our previous results, the present study underlines that besides a highly standardized surgical intervention, the weight loss of surgically treated obesity is influenced by several characteristics such as age and initial body weight, 31 their capacity to spare energy 27 and to activate the sympathetic nervous system. These findings could be useful to better understand the large individual variability of body weight loss obtained by bariatric surgery and, more generally, by any weight reduction program.…”
Section: Discussionmentioning
confidence: 83%
“…For instance, it has been demonstrated that some psychological traits, such as anxiety and excessive health concerns, are linked to a less satisfactory result after gastric bypass [7], whereas patients showing eating disorders are likely to regain weight at long-term follow-up [8,9]. Among the anthropometric characteristics, initial BMI [10,11] plays an important role in surgically induced body weight loss. Diabetes [12] has also been suggested as a predictor of a lesser weight reduction following bariatric surgery.…”
Section: Introductionmentioning
confidence: 99%